Biomass Variations in the Bivalves Fauna of Selected Tidal Flats of East Coast In India - Anandaraj, T. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTThe present study was conducted to study the biomass variations in different wetlands at East coast of India, during August 2011 to December 2011. The 5 different molluscan species such as Meretrix casta, Meretrix menet, Donax cuneatus, Perna viridis and Phaphia textile were collected from 4 different wetlands such as Pichavaram, Poombukar, Karaikal and Nagappattinam. Among the collected species, Meretrix meretrix showed highest value in 62.876 gm (animal weight), 53.087 gm (shell weight), 7.783 gm (Flesh weight), 2.006 gm (Dry weight), 0.984 gm (Ash free dry mass weight), 7.778 gm (water weight) recorded from Pichavaram coast, and Ash weight was highest in 0.921 gm recorded from Nagappattinam coast. The lowest values were recorded from 4 different wet land and 5 different species.